International human resource management and challenges to be overcome - Luciana Campos Lima (Internext: Revista Eletrônica de Negócios Internacionais, 2016)
It was taken as a reference that the IHRM field of study is inherent to the dynamics of structuring business relationships worldwide. This has been favored by the opening of national economies, such as Eastern Europe, China and the former Soviet Union (Homen, Tolfo, 2008), coupled with a GDP stagnation in developed countries and the rise of emerging nations’ consumer markets.